Modulatory effects of an NMDAR partial agonist in MK-801-induced memory impairment. (17th December 2015) - Vishnoi, S.; Raisuddin, S.; Parvez, S.
Highlights: Neurobehavioral deficits induced by MK-801 were inhibited by DCS. DCS counteracted MK-801 induced increase in dopamine level, AChE & MAO activity. DCS controlled the degree of overexpression of c-fos induced by MK-801. Improving NMDAR function by DCS may play vital role in neuropsychiatric disorders. Abstract: Rationale: Acute administration of the N-methyl-d -aspartate (NMDA) non-competitive antagonist, MK-801, impairs novel object recognition (NOR), locomotor activity in open field (OF) and conditioned taste aversion (CTA) in rodents. NMDAR partial agonistd -cycloserine (DCS) reverses these effects in NOR and CTA via modulation of glutamatergic, cholinergic and dopaminergic systems. Objectives and methods: To test this hypothesis, we investigated the effects of DCS, a partial NMDAR agonist, on NOR memory, locomotor activity, and CTA memory in Wistar rats on NMDA-glutamate receptor antagonism by MK-801. The potential involvement of dopaminergic and cholinergic systems in improving cognitive functions was explored. MK-801-induced cognitive deficits were assessed using NOR, OF and CTA paradigms. MK-801-induced dopamine release increase in acetylcholinesterase (AChE), mono amine oxidase (MAO) activity and increase in c-fos expression were also investigated. Results: The effects caused by MK-801 (0.2 mg/kg) were inhibited by administration of the NMDA receptor agonist DCS (15 mg/kg). NOR and CTA paradigms inhibited by MK-801 were attenuated by DCS administration. Moreover, DCS also blocked the MK-801-induced abnormal increase in dopamine content, AChE activity and MAO activity. However, c-fos overexpression was controlled to some extent only. Conclusions: Based on the NMDAR hypo function hypothesis in some neuropsychiatric disorders, our finding suggests that improving NMDAR hypo function by agonist DCS may play a significant role.